Lithium bidirectionally regulates depression- and mania-related brain functional alterations without worsening cognitive function in patients with bipolar disorder - Zhuo, Chuanjun; Chen, Guangdong; Chen, Jiayue; Tian, Hongjun; Ma, Xiaoyan; Li, Qianchen; Yang, Lei; Zhang, Qiuyu; Li, Ranli; Song, Xueqin; Huang, Chunhai (Frontiers in Psychiatry, 2022)
ABSTRACT Background: Lithium monotherapy has been proven to have antidepressant and antimanic effects in patients with bipolar disorder (BP), but the mechanism underlying these bidirectional effects remains poorly understood. The main aim of this study was to test the hypothesis that lithium bidirectionally regulates depression- and mania-related brain functional abnormalities in patients with BP. We also assessed the effects of lithium, alone and in combination with other pharmacological treatments, on patients’ cognitive performance. Methods: We enrolled 149 drug-naïve patients with BP; 99 patients experiencing first depressive episodes were allocated randomly to four treatment groups [lithium (DP/Li), lithium with lamotrigine (LTG; DP/Li+LTG), LTG (DP/LTG), and valproate (VPA) with LTG (DP/VPA+LTG)], and 50 experiencing first manic episodes were allocated to two treatment groups (MA/Li and MA/VPA). For comparative analysis, 60 age-matched healthy individuals were also recruited. Whole-brain global and regional resting-state cerebral blood flow (rs-CBF) and cognitive alterations were examined before and after 12-week treatment. Results: DP/Li+LTG, and to a lesser extent DP/Li, alleviated the depression-related reduction in rs-CBF. MA/VPA and MA/Li reversed the mania-related elevation of rs-CBF completely and partially, respectively. Lithium alone improved cognitive performance during depressive and manic episodes; other tested treatments have no such effect or worsened cognitive ability. Conclusions: lithium bidirectionally regulates depression- and mania-associated brain functional abnormalities in patients with BP. Lithium monotherapy has a better antimanic effect than VPA, is superior to other tested treatments in improving cognition during the course of BP, and has satisfactory antidepressant effects in patients with BP.